Food Security Simulator Nigeria Launch Event Highlights - Ecker, Olivier; Andam, Kwaw S. (CGIAR System Organization, 2023)
This video highlight was from the Food Security Simulator Nigeria launch on 31 Oct. 2023 in Abuja, Nigeria. The Food Security Simulator Nigeria was developed by the International Food Policy Research Institute (IFPRI), under the CGIAR Research Initiative on National Policies and Strategies (NPS), with important contributions from the National Bureau of Statistics (NBS), Federal Ministry of Agriculture and Food Security (FMAFS), Federal Ministry of Humanitarian Affairs, and Poverty Alleviation Reduction (FMHAPA), and other partners in Nigeria during the validation processes of the tool. This work was made possible by support from the CGIAR Trust Fund.